SAT0227 Urinary heparanase activity is elevated in patients with lupus nephritis and correlate with protein excretion. (23rd January 2014) - Kim, K.-J.; Kim, J.-Y.; Park, S.-J.; Baek, I.-W.; Yoon, C.-H.; Kim, W.-U.; Cho, C.-S.
Abstract : Background: The heparin sulphate proteoglycans (HSPGs) in the glomerular basement membrane (GBM) play an important role in the charge-selective permeability of the glomerular filter. The β-D-endoglycosidase heparanase has been proposed to be important in the pathogenesis of proteinuria by selectively degrading the negatively charged side chains of HSPGs within the GBM in various forms of glomerulonephritis. Objectives: To evaluate plasma and urinary activity of heparanase and to determine association between its levels and proteinuria in patients with lupus nephritis Methods: Plasma from 50 patients with systemic lupus erythematosus and 10 normal healthy subjects were collected. The clinical and laboratory data of the patients were obtained at the time of sampling. Thirty three patients had a history of lupus nephritis and their urine was also collected. Proteinuria was defined as more than 0.5 g/day. Heparanase activity of plasma and urine was determined by a commercially available kit. Results: Plasma heparanase activity was significantly elevated in SLE patients compared to controls (745.2±112.5 vs . 203.6±87.1 mIU/ml, p =0.039). Twenty five of patients with lupus nephritis showed significant proteinuria and their heparanase activity was not different from those without proteinuria (607.0±123.1 vs . 700.8±224.3 mIU/ml, p =0.725). On the other hand, urinary heparanase activity of patients with proteinuria was significantly elevated compared with those of patients without proteinuria (1092.1±334.2 vs . 93.3±42.8 mIU/ml, p =0.008). Moreover, urinary heparanase activity was positively correlated with 24 hours protein excretion (γ =0.546, p =0.016). Urinary heparanase activity showed an inverse correlation with complement haemolytic activity (CH50) (γ = -0.454, p =0.030) and had a tendency to associate negatively with C3 and C4 complement levels (γ = -0.331, p =0.123 and γ = -0.299, p =0.166, respectively). Conclusions: Urinary heparanase activity was elevated in patients with lupus nephritis and reflect the urinary protein excretion, suggesting a potential role in the pathogenesis of proteinuria in lupus nephritis. Disclosure of Interest: None Declared